RETRACTED: Green finance, green energy, and green revolution: An impulse response function of food security in developing economies - Huan, Yu; Sun, Zhaojun; Ali, Muhammad; Yan, Ran; Ur Rahman, Zia (Frontiers in Environmental Science, 2022)
Recently, it has observed that fossil fuel utilization increased to manage the issue of food insecurity; however, it has increased the risk of environmental degradation and land availability. Therefore, the role of a farmer is to ensure food security; with the assistance of the green revolution, green finance and green energy has increased manifold. For this purpose, the current study utilized a time-series dataset between 2017-2019 to evaluate the relationship between green finance, green energy, and the green revolution with food security. This objective has been considered with modern econometric methods, including the autoregressive distributed lag model and impulse response. As a result, the ARDL model affirmed cointegration between the green revolution, green finance, and green energy with food security. According to the results, food security will rise by 0.11 percent, 0.16 percent, 0.15 percent, and 0.4 percent, with a 1 percent increase in green finance, irrigation, pesticides, and fossil fuel, respectively. Furthermore, based on the diagnostic statistics, the ARDL model's credibility, stability, and reliability were correct. In light of these findings and the impulse response function, all relevant factors will favor future food security. Finally, this study suggested that the public and commercial sectors should invest significantly in R&D to produce organic chemicals and agricultural methods that preserve soil fertility and reduce environmental degradation.